Epigenetic Manipulation of Psychiatric Behavioral Disorders Induced by Toxoplasma gondii - Yin, Kun; Xu, Chao; Zhao, Guihua; Xie, Huanhuan (Frontiers in Cellular and Infection Microbiology, 2022)
Toxoplasma gondii is known to have a complex life cycle and infect almost all kinds of warm-blooded animals around the world. The brain of the host could be persistently infected by cerebral cysts, and a variety of psychiatric disorders such as schizophrenia and suicide has been reported to be related with latent toxoplasmosis. The infected animals showed fear reduction and a tendency to be preyed upon. However, the mechanism of this “parasites manipulation” effects have not been elucidated. Here, we reviewed the recent infection prevalence of toxoplasmosis and the evidences of mental and behavioral disorders induced by T. gondii, discussed the related physiological basis including dopamine dysregulation and gamma-aminobutyric acid(GABA) pathway, and the controversial opinion of the necessary for cerebral cysts existence. Based on the recent advances, we speculated that the neuroendocrine programs and neurotransmitter imbalance may play a key role in this process. Simultaneously, studies in evaluation of the expression pattern of related genes, LncRNAs and mRNAs of the host, provides a new point for understanding the mechanism of neurotransmitter dysfunction induced by parasite manipulation. Therefore, we summarized the animal models, T. gondii strains and behavioral tests used in the related epigenetic studies and the responsible epigenetic processes；pinpoints opportunities and challenges in future researches including the causality evidence of human psychiatric disorders, the statistical analysis for rodent infected host to be more vulnerable preyed upon, and identification of responsible genes and drug targets through epigenetic.